2008
DOI: 10.1210/en.2008-0369
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Proliferation of Periosteal Osteoblast Progenitors Are Differentially Regulated by Estrogens and Intermittent Parathyroid Hormone Administration

Abstract: The periosteum is now widely recognized as a homeostatic and therapeutic target for actions of sex steroids and intermittent PTH administration. The mechanisms by which estrogens suppress but PTH promotes periosteal expansion are not known. In this report, we show that intermittent PTH(1-34) promotes differentiation of periosteal osteoblast precursors as evidenced by the stimulation of the expression or activity of alkaline phosphatase as well as of targets of the bone morphogenetic protein 2 (BMP-2) and Wnt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 47 publications
5
59
0
1
Order By: Relevance
“…Indeed, these observations lead us to propose that PTH down-regulation of Sost in osteocytes is mediated by a two-step process [i.e., through PTH1R activation and cAMP/ERK signaling (probably a rapid and short term effect)], that is independent of Postn (20), then through Postn production and an autocrine/paracrine activation of integrin signaling, leading to a prolonged suppression of Sost expression. These latter observations are consistent with a direct activation of Wnt-β-catenin signaling by PTH in osteoblasts (28,29).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, these observations lead us to propose that PTH down-regulation of Sost in osteocytes is mediated by a two-step process [i.e., through PTH1R activation and cAMP/ERK signaling (probably a rapid and short term effect)], that is independent of Postn (20), then through Postn production and an autocrine/paracrine activation of integrin signaling, leading to a prolonged suppression of Sost expression. These latter observations are consistent with a direct activation of Wnt-β-catenin signaling by PTH in osteoblasts (28,29).…”
Section: Discussionsupporting
confidence: 87%
“…(14) When PTH is used intermittently as a treatment for osteoporosis, it similarly stimulates bone turnover increasing the amount of younger, less mineralized bone. (15) In contrast to hyperparathyroidism, however, this increased turnover seen with intermittent administration appears to favor anabolism, rather than catabolism, stimulating osteoblast progenitors, (16,17) inhibiting osteoblast apoptosis (18) and increasing bone density at the lumbar spine and hip while decreasing BMD at the distal radius. (19,20) When PTH therapy for osteoporosis is discontinued, spinal and hip gains in BMD are gradually lost and radial BMD increases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mice exhibit profound sex-dependent differences in the pulsatility and amplitude of GH secretion that results in sexually dimorphic expression of GH target genes (48), providing one possible explanation for the gender specificity of the phenotypes the ΔGHR mice. Alternatively, it is known that osteoblasts that reside at the periosteal surface arise from precursors distinct from osteoblasts in the trabecular compartment, and evidence suggests these cells may have a differential response to PTH and estrogen (49). In addition, numerous studies, in both humans and animal models, have demonstrated that estrogen is predominantly responsible for periosteal expansion in males, converted from androgens by aromatase (50).…”
Section: Discussionmentioning
confidence: 99%